A Tobacco Syringe Agroinfiltration-Based Method for a Phytohormone Transporter Activity Assay Using Endogenous Substrates - Zhao, Jiangzhe; Ju, Min; Qian, Jiayun; Zhang, Mengyuan; Liu, Ting; Zhang, Kewei (Frontiers in Plant Science, 2021)
Phytohormones are a group of small chemical molecules that play vital roles in plant development, metabolism, and stress responses. Phytohormones often have distinct biosynthesis and signaling perception sites, requiring long- or short-distance transportation. Unlike biosynthesis and signal transduction, phytohormone transport across cells and organs is poorly understood. The transporter activity assay is a bottleneck for the functional characterization of novel phytohormone transporters. In the present study, we report a tobacco syringe agroinfiltration and liquid chromatography tandem mass spectrometry (TSAL)-based method for performing a phytohormone transporter activity assay using endogenous hormones present in tobacco (Nicotiana benthamiana) leaves. A transporter activity assay using this method does not require isotope-labeled substrates and can be conveniently performed for screening multiple substrates by using endogenous hormones in tobacco leaves. The transporter activities of three known hormone transporters, namely AtABCG25 for abscisic acid, AtABCG16 for jasmonic acid, and AtPUP14 for cytokinin, were all successfully validated using this method. Using this method, cytokinins were found to be the preferred substrates of an unknown maize (Zea mays) transporter ZmABCG43. ZmABCG43 transporter activities toward cytokinins were confirmed in a cytokinin long-distance transport mutant atabcg14 through gene complementation. Thus, the TSAL method has the potential to be used for basic substrate characterization of novel phytohormone transporters or for the screening of novel transporters for a specific phytohormone on a large scale.